2014
DOI: 10.1039/c4nr01350f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and electronic properties of a thiolate-protected Au24 nanocluster

Abstract: Solving the total structures of gold nanoclusters is of critical importance for understanding their electronic, optical and catalytic properties. Herein, we report the X-ray structure of a charge-neutral Au24(SCH2Ph-(t)Bu)20 nanocluster. This structure features a bi-tetrahedral Au8 kernel protected by four tetrameric staple-like motifs. Electronic structure analysis is further carried out and the optical absorption spectrum is interpreted. The Au24(SCH2Ph-(t)Bu)20, Au23(S-c-C6H11)16 and Au25(SCH2CH2Ph)18 nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
479
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(506 citation statements)
references
References 74 publications
23
479
1
3
Order By: Relevance
“…A couple of selenolate-protected Au NCs have also been recently elucidated with icosahedral or small Au 8 core structures [31,32]. In the last few years, a number of surface structures in addition to the monomeric and dimeric staple-like motifs were identified such as a trimeric staple-like motif [28], tetrameric staple-like motif [29,30], μ 3 sulfide coordination [25], bridging thiolate motif [24], and ring-like motifs (long Au-SR oligomers) [27,33]. Figure 1 presents the diversity of thiolate-protected Au NC structures.…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of selenolate-protected Au NCs have also been recently elucidated with icosahedral or small Au 8 core structures [31,32]. In the last few years, a number of surface structures in addition to the monomeric and dimeric staple-like motifs were identified such as a trimeric staple-like motif [28], tetrameric staple-like motif [29,30], μ 3 sulfide coordination [25], bridging thiolate motif [24], and ring-like motifs (long Au-SR oligomers) [27,33]. Figure 1 presents the diversity of thiolate-protected Au NC structures.…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%
“…Since the elucidation of the Au 102 (SR) 44 NC in 2007 [19], the catalog of possible Au core geometries and stabilizing surface structures from solved crystal structures and DFT predictions has grown significantly [20]. To date, icosahedral, face-centered-cubic (FCC)-ordered and smaller Au core ( < 13 Au atoms) structures have been reported crystallographically for various Au n (SR) m sizes [19,[21][22][23][24][25][26][27][28][29][30]. A couple of selenolate-protected Au NCs have also been recently elucidated with icosahedral or small Au 8 core structures [31,32].…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%
“…Pei and co-workers predicted the geometry of the synthesized clusters through DFT calculations of Au 24 (SCH 3 ) 20 . 27 Thereafter, Jin et al 28 characterized Au 24 (SCH 2 Ph-t Bu) 20 (SCH 2 Ph-t Bu = 4-tert-butylphenylmethanethiolate) by single-crystal X-ray structural analysis. However, the obtained geometric structure was different from that predicted by Pei's group.…”
Section: Ligand Exchangementioning
confidence: 99%
“…Recent studies on the thiolate stabilized Au clusters indicated their varied core structures such as the icosahedral Au core 7,12,21 the face-centered-cubic (FCC)-like Au core [8][9][10][11] and others 6,14 . Among these clusters, FCC-like Au clusters attract significant amount of interest because these ultrasmall particles exhibit unexpected core structure of FCC geometry, similar to that of bulk gold.…”
mentioning
confidence: 99%
“…size-controlled synthesis of these Au clusters allows for a variety of size-specific studies [5][6][7][8][9][10][11][12][13][14][15] such as the bonding and electronic properties 3,[16][17][18][19][20] . Recent studies on the thiolate stabilized Au clusters indicated their varied core structures such as the icosahedral Au core 7,12,21 the face-centered-cubic (FCC)-like Au core [8][9][10][11] and others 6,14 .…”
mentioning
confidence: 99%